HUBUNGAN TERAPI MODALITAS INDIVIDU DAN KELOMPOK PADA PASIEN GANGGUAN JIWA TERHADAP KESIAPSIAGAAN MENGHADAPI ANCAMAN BENCANA GEMPA BUMI DI BADAN LAYANAN UMUM DAERAH RSJ ACEH - Sarah Ainun; Muchlisin ZA; Imran Imran (Jurnal Kedokteran Syiah Kuala, 2017)
This study  aims to determine the relationship of increasing the parameters of knowledge, attitude, and action through individual therapy and group activity therapy in improving the preparedness of patients facing earthquake disaster at mental hospital. This reserch methode use Experimental design with true experiments model design (pre test-post test control group design). The sampling technique used is simple random sampling with sample size of 30 patients drawn from 9 intermediate inpatient rooms. Patients were divided into three group; 10 controls, 10 individual, and 10  group activity therapy. Data were collected through interviews and obsevation. The results showed that there was no increase of post-test in the control group on the parameters of knowledge, attitude, and action. The highest increase was found in the action parameter of 10.7 ( increase 60%) for individual therapy 7.3 (increased 52.52%) for group actifity therapy.. Therapy of individual modalities and therapy group activities are indicates existence in improving the knowledge, attitudes, and actions of patients in the face of the earthquakes.